Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan: Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan - Martinus Febryanto Andy Pratama; Wahyu Prabawati Putri Handayani (Jurnal Sosial Ekonomi Bisnis, 2022)
The purpose of this study was to examine the significance of the effect of reward and punishment on employee performance at CV Champion Jaya Sejahtera. We used saturated sampling technique for obtaining 52 employees meeting subject from CV Champion Jaya Sejahtera. Multiple linear regression analysis was employed to describe the effect reward and punishment effect on employee performance. T-test shows that the reward has a significant positive effect on the work discipline employees of CV Champion Jaya Sejahtera. While punishment has insignificant positive effect on employee performance variable